(3GdSQ GdQHGfj aj GdYde GdejRGfjs - (3GdCRfjbj, Ydj LdHj Hf NSQh, J (B1018 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj JbOSJ PGJg afj deG hUdJ Edi MbGFb GdYde GdEdgj ef cdGe GdGeGe GdgeGe GdeSei HNWjH GdHjGf dYdj QV Gddg Yfg Ydi eG aSQg GdaGVd GdLdOcj aj GdJbQjH s
(3BNQgG (B:s
(3hbO cTaJ ajg LejY GdLhGgQ GdeQehRGJ GdeMRhfGJ aj cJH GdcMeGA ef GdSGda Edi GdBf hdhdG aVd Gddg Ydjce UMGFa GdcJH HgPg GdLhGgQ GdefXheI aj Sdc GdHjGf cOQQ GdchGcH Jes
(3JHUQI GdeDda (B:s
(3hQO GSeg aj HYV GdagGQS (B: (3Ydj Hjcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2\416s
(3eYLe GdJGQjN GdJQGK (B3\2232 (5968 )s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs